Cost comparison analysis of laparoscopic versus open aortobifemoral bypass surgery: a randomized controlled trial - Sahba M; Krog AH; Pettersen EM; Wisløff T; Rogne KG; Sundhagen JO; Kazmi SSH (Open Access Journal of Clinical Trials, 2019)
M Sahba,1 AH Krog,1 EM Pettersen,2 T Wisløff,3,4 KG Rogne,5 JO Sundhagen,6 SSH Kazmi6,71Department of Vascular Surgery, Ostfold Central Hospital, Grålum, Norway; 2Department of Vascular Surgery, Sørlandet Hospital HF, Kristiansand, Norway; 3Department of Infectious Disease Epidemiology and Modelling, Norwegian Institute of Public Health, Oslo, Norway; 4Department of Health Management and Health Economics, University of Oslo, Oslo, Norway; 5Economy Department, Oslo University Hospital, Oslo, Norway; 6Department of Vascular Surgery, Division of Cardiovascular and Pulmonary Diseases, Oslo University Hospital, Oslo, Norway; 7Faculty of Medicine, Oslo University, Oslo, NorwayBackground: Laparoscopic aortobifemoral bypass (LABFB) surgery has become an established treatment procedure for aortoiliac occlusive disease (AIOD), Trans-Atlantic Inter-Society Consensus II (TASC II), type D lesions. However, studies with an economic evaluation of this procedure are sparse. The main purpose of our study was to compare the costs of LABFB and open aortobifemoral bypass (OABFB) surgery.Patients and methods: This is a substudy of a larger randomized controlled prospective multicenter trial, Norwegian Laparoscopic Aortic Surgery Trial (NLAST). Perioperative data were collected on 70 patients undergoing surgery for AIOD, TASC type D lesions. Thirty-four patients were randomized to LABFB and 36 patients to OABFB. Treatment costs were calculated for the two operative treatments until 30 postoperative days. In addition to fixed and variable costs, direct and indirect costs were also included.Results: The mean total cost of LABFB was 19,798 € and for OABFB 34,016 € until 30 postoperative days. Laparoscopic procedure was 14,218 € less costly than the open procedure. The main factor leading to less cost of LABFB was shorter length of hospital stay (mean 5.3 days, 95% CI 4.1–6.5) as compared to OABFB (mean 10.1 days, 95% CI 7.5–12.6). Ten patients, three in the LABFB and seven in the OABFB group, had complications that resulted in reoperations within the 30 postoperative days. The mean cost of treatment for the complicated patients was 49,349 € and 82,985 €, respectively, for LABFB and OABFB.Conclusion: Laparoscopic aortobifemoral bypass procedure costs less than open aortobifemoral bypass for the treatment of advanced aortoiliac occlusive disease.Keywords: cost comparison, laparoscopic aortobifemoral bypass, laparoscopic treatment